Response of Non-Irrigated Peanut to Multiple Rate Delayed Flumioxazin Applications - Nicholas L. Hurdle; Timothy L. Grey; Juliana de Souza Rodrigues; W. Scott Monfort (Agronomy)
Flumioxazin is crucial for peanut weed management across the United States with over 75% of growers applying it to control troublesome weed species. For maximum peanut yield, it is essential that weed control is maintained during weeks three through eight after planting. Peanut injury due to flumioxazin PRE applied has been noted under unfavorable moisture or weather conditions, but also due to delays in application as growers plant hundreds of hectares on their farms. Research in Georgia (GA) investigated the response of non-irrigated peanut to flumioxazin PRE applied from 0 to 107 g ai/ha at 0 to 14 d after planting for cultivar Georgia-16HO. Trends during the 2020 through 2022 growing seasons indicated that as rate and time after planting of application increased, injury increased. Over 50% injury was noted in Tift County and 24% in Sumter County during the 2021 growing season. Peanut pod yield decreased while flumioxazin rate increased and time of application after planting was delayed in Tift County, but no differences were noted in Sumter County, potentially due to soil adsorption of the herbicide. Yield differences of up to 800 kg/ha were noted when comparing no herbicide being applied to the full application rate. The recorded injury coincided with large amounts of rainfall at both locations. It was also noted that peanut may be most sensitive to flumioxazin application injury between days seven and ten after planting.